2021
DOI: 10.1186/s12872-020-01820-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of education delivery through multimedia and text messaging on the psychological parameters of patients scheduled for coronary angiography: a single-blind randomized controlled clinical trial

Abstract: Background Angiography is a highly effective invasive method for diagnosing coronary artery diseases but can lead to certain psychological problems such as stress, anxiety, and depression. This study aimed to compare the effects of education delivery through multimedia DVD content or text messaging in comparison with conventional printed pamphlets on the psychological parameters of patients scheduled for angiography. Methods This study was a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The study conducted by Torabizadeh et al and Boyer et al also showed that the multimedia educational caused a reduce anxiety in patients with heart diseases. This finding is consistent with the present study [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 95%
“…The study conducted by Torabizadeh et al and Boyer et al also showed that the multimedia educational caused a reduce anxiety in patients with heart diseases. This finding is consistent with the present study [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 95%
“…Specifically, in the Hu et al study ( Hu et al, 2020 ), the intervention group watched the educational video as often as they wanted, unlike the control group, who observed it only once. In all the other studies ( Bowers et al, 2017 , Sun et al, 2020 , Lattuca et al, 2018 , Jamshidi et al, 2013 , Torabizadeh et al, 2021 , Xia et al, 2019 , Pearson et al, 2005 , Wouters et al, 2019 , Ayasrah and Ahmad, 2016 , Ahlander et al, 2018 , Ketelaars et al, 2017 , Ruffinengo et al, 2009 , Tugwell et al, 2018 , Rigatelli et al, 2009 , Habibzadeh et al, 2018 ), the intervention groups watched the educational video, contrary to the control group who did not see the educational video.…”
Section: Resultsmentioning
confidence: 93%
“…The articles analyzed used experimental methods, and thirteen of them presented themselves as randomized clinical trials. ( Bowers et al, 2017 , Sun et al, 2020 , Lattuca et al, 2018 , Jamshidi et al, 2013 , Torabizadeh et al, 2021 , Xia et al, 2019 , Pearson et al, 2005 , Ayasrah and Ahmad, 2016 , Ahlander et al, 2018 , Ketelaars et al, 2017 , Ruffinengo et al, 2009 , Tugwell et al, 2018 , Rigatelli et al, 2009 , Habibzadeh et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Educating patients about what to expect before and during the colonoscopy can reduce the stress of the unknown. A recent randomized controlled trial assessing the use of DVDs for coronary angiography showed that it is more effective than conventional pamphlets in controlling anxiety and stress [ 44 ]. There are patient-associated barriers particular to accessing the educational material on a DVD, including lack of access to a DVD player, unfamiliarity with usage, and inability to use the interactive features.…”
Section: Discussionmentioning
confidence: 99%